Characterization of the Antigen-Specific CD4+ T Cell Response Induced by Prime-Boost Strategies with CAF01 and CpG Adjuvants Administered by the Intranasal and Subcutaneous Routes - Ciabattini, Annalisa; Prota, Gennaro; Christensen, Dennis; Andersen, Peter; Pozzi, Gianni; Medaglini, Donata (Frontiers in Immunology, 2015)
The design of heterologous prime-boost vaccine combinations that optimally shape the immune response is of critical importance for the development of next generation vaccines. Here we tested different prime-boost combinations using the tuberculosis vaccine antigen H56 with CAF01 or CpG ODN 1821 adjuvants, administered by the parenteral and nasal routes. By using peptide-MHC class II tetramers, antigen-specific CD4+ T cells were tracked following primary and booster immunizations. Both parenteral priming with H56 plus CAF01 and nasal priming with H56 plus CpG elicited significant expansion of CD4+ tetramer-positive T cells in the spleen, however only parenterally primed cells responded to booster immunization. Subcutaneous priming with H56 and CAF01 followed by nasal boosting with H56 and CpG showed the greater expansion of CD4+ tetramer-positive T cells in the spleen and lungs compared to all the other homologous and heterologous prime-boost combinations. Nasal boosting exerted a recruitment of primed CD4+ T cells into lungs that was stronger in subcutaneously than nasally primed mice, in accordance with different chemokine receptor expression induced by primary immunization. These data demonstrate that subcutaneous priming is fundamental for eliciting CD4+ T cells that can be efficiently boosted by the nasal route and results in the recruitment of antigen-experienced cells into the lungs. Combination of different vaccine formulations and routes of delivery for priming and boosting is a strategic approach for improving and directing vaccine-induced immune responses.